1996
DOI: 10.1093/clinids/22.supplement_1.s3
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Rifabutin

Abstract: Rifabutin is a spiro-piperidyl-rifamycin derived from rifamycin-S. It is structurally related to rifampin and shares many of its properties. Rifabutin has a broad spectrum of antimicrobial activity. It is considerably more active than rifampin in vitro against the Mycobacterium avium complex (MAC), Mycobacterium tuberculosis, and Mycobacterium leprae. It also is active against most atypical mycobacteria, including Mycobacterium kansasii, but Mycobacterium chelonae is relatively resistant. Rifabutin also is act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
1
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 65 publications
4
107
1
2
Order By: Relevance
“…The DNA sequences of the rpoB whole gene demonstrated that all of the 362 rifamycin-resistant isolates had missense mutations in the rpoB entire gene, while 30 susceptible isolates and 1 reference strain (strain H37Rv) of M. tuberculosis had no mutations in the rpoB whole gene, which was in line with the previous findings that the susceptibility to rifampin and that to rifabutin in M. tuberculosis are closely correlated with mutation of the rpoB gene (9,12,18). Furthermore, more than 95% of RIF r isolates in our study possessed mutations inside the RRDR of the rpoB gene, which was consistent with the data reported by previous researchers (10,17,11).…”
Section: Discussionsupporting
confidence: 87%
“…The DNA sequences of the rpoB whole gene demonstrated that all of the 362 rifamycin-resistant isolates had missense mutations in the rpoB entire gene, while 30 susceptible isolates and 1 reference strain (strain H37Rv) of M. tuberculosis had no mutations in the rpoB whole gene, which was in line with the previous findings that the susceptibility to rifampin and that to rifabutin in M. tuberculosis are closely correlated with mutation of the rpoB gene (9,12,18). Furthermore, more than 95% of RIF r isolates in our study possessed mutations inside the RRDR of the rpoB gene, which was consistent with the data reported by previous researchers (10,17,11).…”
Section: Discussionsupporting
confidence: 87%
“…RFB has been proposed as an alternative to RIF in the treatment of TB in transplant patients. It is as effective as RIF 41 and allows better control of plasma concentrations of immunosuppressants; as a result, it reduces the risk of acute rejection. 42 However, although drug interactions are less of a problem in comparison with RIF, they may still occur, and close monitoring of immunosuppressants is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of analgesic nephropathy decreased substantially in all countries after the banning of phenacetin, 2 with the decrease in the countries that banned the drug later following exactly the time course observed earlier in Australia. An evaluation of all the epidemiologic studies of nonnarcotic analgesics 3 revealed no evidence that combination drugs are more nephrotoxic than single analgesics at equipotent doses provided they do not contain phenacetin. The case-control studies show a very uniform picture: odds ratios for analgesics containing phenacetin are extremely high (up to 19), whereas the odds ratios for single analgesics and for combination drugs (without phenacetin) are in the same range (i.e., 2 to 3) ( Table 2 of the article).…”
Section: Analgesic Nephropathymentioning
confidence: 99%
“…Several experimental studies [1][2][3] have shown the difficulty of inducing renal papillary necrosis with single analgesics such as phenacetin, paracetamol, and aspirin, in contrast to the ease of doing so with such analgesic mixtures as aspirin, phenacetin, and caffeine; aspirin, acetaminophen, and caffeine; and aspirin, salicylamide, and caffeine. Furthermore, Duggin 4 and others have demonstrated the synergistic nephrotoxic effect of the prostaglandin H synthasedependent co-oxidation of acetaminophen to a cytotoxic metabolite with the capacity of aspirin to deplete renal glutathione in animals.…”
Section: Analgesic Nephropathymentioning
confidence: 99%
See 1 more Smart Citation